Hypoalgesia and Conditioned Pain Modulation in Blood Flow Restriction Resistance Exercise - Yang, Jinghui; Rolnick, Nicholas; Merriwether, Ericka; Rao, Smita (International Journal of Sports Medicine, 2024)
We compared the magnitude of exercise-induced hypoalgesia and conditioned pain modulation between blood-flow restriction (BFR) resistance exercise (RE) and moderate-intensity RE. Twenty-five asymptomatic participants performed unilateral leg press in two visits. For moderate-intensity RE, subjects exercised at 50% 1RM without BFR, whereas BFR RE exercised at 30% 1RM with a cuff inflated to 60% limb occlusion pressure. Exercise-induced hypoalgesia was quantified by pressure pain threshold changes before and after RE. Conditioned pain modulation was tested using cold water as the conditioning stimulus and mechanical pressure as the test stimulus and quantified as pressure pain threshold change. Difference in conditioned pain modulation pre- to post-RE was then calculated. The differences of RE on pain modulations were compared using paired t-tests. Pearson’s r was used to examine the correlation between exercise-induced hypoalgesia and changes in conditioned pain modulation. We found greater hypoalgesia with BFR RE compared to moderate-intensity RE (p=0.008). Significant moderate correlations were found between exercise-induced hypoalgesia and changes in conditioned pain modulation (BFR: r=0.63, moderate-intensity: r=0.72). BFR RE has favorable effects on pain modulation in healthy adults and the magnitude of exercise-induced hypoalgesia is positively correlated with conditioned pain modulation activation.
Keywords: blood-flow restriction; exercise-induced hypoalgesia; conditioned pain modulation; resistance exercise; sex; descending pain inhibition